Apuntes constitucionales sobre el proceso especial de dictado de medidas de protección - Ley 30364 - Calvo Daza, Elsa (2025)
This article addresses the constitutional tensions inherent in the special procedure for issuing protection measures under Law 30364, particularly in relation to fundamental guarantees such as due process, the presumption of innocence, and the right to defense. It asserts that these guarantees are not violated but must be interpreted contextually, in light of the procedure’s urgent and preventive character. The analysis highlights the sui generis and urgent nature of the protective stage, its alignment with binding international human rights standards - most notably Convention on the Elimination of AllForms of Discrimination against Women and the Belém do Pará Convention– and the centrality of the reinforced due diligence standard in ensuring effective protection for victims of gender-based violence. It is argued that the principle of proportionality, when applied through a gender-sensitive lens, reconciles the imperative of immediate and effective victim protection with the preservation of the respondent’s fundamental rights, without eroding the protective function of the process. The article advances the proposal of applying a reinforced proportionality test to the constitutional review of protection measures. This test incorporates interpretative tools such as the in dubio pro victim principle and the due diligence standard specific to cases of violence against women, Chile safeguarding the essential core of procedural guarantees. Through this framework, the special procedure emerges as a constitutionally sound and necessary mechanism to address gender-based violence in accordance with both domestic constitutional principles and international human rights obligations.